Handgrip strength: a reliable predictor of postoperative early ambulation capacity for the elderly with hip fracture - Chang, Chih-Mai (BMC Musculoskelet Disord, 2021)
BACKGROUNDS: A common sequela of hip fracture is loss of ambulation capacity. Prediction of postoperative ambulation capacity is important for surgical and rehabilitation decision making. Handgrip strength is a quick and convenient tool for evaluating postoperative functional ability and outcome in variety of clinical conditions for the elderly and is associated with the use of walking aids. We propose that handgrip strength may be a good predictor for postoperative early ambulation. The purpose of our study was to investigate the contribution of handgrip strength in the prediction of postoperative early ambulation capacity in elderly hip fracture patients. METHODS: Clinical data of patients with low-energy hip fractures who received surgery from Jan 2018 to Dec 2019 were prospectively collected. The correlations of ambulation time with complication rate, age, gender, injured side, fracture classifications, surgical procedure, body mass index (BMI), and handgrip strength were analyzed. RESULTS: Sixty-three hip fracture patients were included in this study. Patients whose ambulation time was less than 3 days after the operation had significantly fewer postoperative complications (P = 0.006). Handgrip strength showed the strongest correlation with postoperative early ambulation capacity (P = 0.004). The handgrip strength threshold value for early ambulation was found to be 20.5 kg for male patients and 11.5 kg for female patients. CONCLUSION: Handgrip strength testis a quick and convenient tool for predicting postoperative early ambulation capacity. In elderly Asians, male patients with a handgrip strength above 20.5 kg and female patients with a handgrip strength above 11.5 kg suggest a high likelihood of early postoperative ambulation and a lower risk of complications after the hip surgery.